Achondroplasia natural history study (CLARITY): 60-year experience in orthopedic surgery from four skeletal dysplasia centers - Nickolas J. Nahm; W. G. Stuart Mackenzie; William G. Mackenzie; Ethan Gough; S. Shahrukh Hashmi; Jacqueline T. Hecht; Janet M. Legare; Mary Ellen Little; Peggy Modaff; Richard M. Pauli; David F. Rodriguez-Buritica; Maria Elena Serna; et al. (Orphanet Journal of Rare Diseases, 2023)
Abstract Background The purpose of this study was to describe the frequency and risk factors for orthopedic surgery in patients with achondroplasia. CLARITY (The Achondroplasia Natural History Study) includes clinical data from achondroplasia patients receiving treatment at four skeletal dysplasia centers in the United States from 1957 to 2018. Data were entered and stored in a Research Electronic Data Capture (REDCap) database. Results Information from one thousand three hundred and seventy-four patients with achondroplasia were included in this study. Four hundred and eight (29.7%) patients had at least one orthopedic surgery during their lifetime and 299 (21.8%) patients underwent multiple procedures. 12.7% (n = 175) of patients underwent spine surgery at a mean age at first surgery of 22.4 ± 15.3 years old. The median age was 16.7 years old (0.1–67.4). 21.2% (n = 291) of patients underwent lower extremity surgery at a mean age at first surgery of 9.9 ± 8.3 years old with a median age of 8.2 years (0.2–57.8). The most common spinal procedure was decompression (152 patients underwent 271 laminectomy procedures), while the most common lower extremity procedure was osteotomy (200 patients underwent 434 procedures). Fifty-eight (4.2%) patients had both a spine and lower extremity surgery. Specific risk factors increasing the likelihood of orthopedic surgery included: patients with hydrocephalus requiring shunt placement having higher odds of undergoing spine surgery (OR 1.97, 95% CI 1.14–3.26); patients having a cervicomedullary decompression also had higher odds of undergoing spine surgery (OR 1.85, 95% CI 1.30–2.63); and having lower extremity surgery increased the odds of spine surgery (OR 2.05, 95% CI 1.45–2.90). Conclusions Orthopedic surgery was a common occurrence in achondroplasia with 29.7% of patients undergoing at least one orthopedic procedure. Spine surgery (12.7%) was less common and occurred at a later age than lower extremity surgery (21.2%). Cervicomedullary decompression and hydrocephalus with shunt placement were associated with an increased risk for spine surgery. The results from CLARITY, the largest natural history study of achondroplasia, should aid clinicians in counseling patients and families about orthopedic surgery.